Climate change and water‐related ecosystem services: impacts of drought in California, USA. Issue 12 (27th December 2016) - Chang, Heejun; Bonnette, Matthew Ryan
Abstract: We investigated the potential impacts of climate change on water‐related ecosystem services (WES). Based on the review of the recent literature, we concluded that climate change will have substantial effects on provisioning, regulating, and cultural WES via changes in the distribution and value of water over space and time. However, the effects of climate change on specific WES will be different depending on the extent of the impact of such changes in the distribution of water and the adaptive capacity of the region's biophysical and social system. The 2015 California drought provides an excellent example of the cascading effects of climate change on multiple WES. Declining streamflow and the concomitant rising stream temperatures have immediately threatened the provision of drinking water and hydropower generation and threatened the health of ecosystems that rely on water. The secondary effects of drought on WES are widespread across different water‐dependent industries, including water‐based recreation. The findings of our study also show that the impacts of climate change will differ by location, suggesting a need for a place‐based flexible climate adaptation strategy. We also suggest that future research directions include the examination of: (1) the multiple cascading effects of climate change on potential synergies and tradeoffs among different WES, (2) the specific effects of changing climate and the connectivity of WES from upstream to downstream WES users, (3) the changing value of WES over space and time under changing climates, and (4) the effectiveness of various climate adaptation measures on the whole suite of WES.